2015
DOI: 10.3390/atmos6101422
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Indoor and Outdoor PM2.5 in Three Schools in the City of Rome

Abstract: Abstract:In Italy, children spend up to 30% of their time in school institutions; for this reason, the evaluation of indoor air quality in schools constitutes a necessary step forward in the direction of child health protection. In this study, we investigated the chemical composition of PM2.5 collected simultaneously indoor and outdoor in three primary schools in Rome. Seasonal variations between winter and spring/summer were evaluated, as well as the role of the main macro-sources of PM (soil, sea, traffic, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 40 publications
4
34
0
Order By: Relevance
“…It is, however, important to underline that the good correlation founded in some studies [40] does not necessarily imply a complete correspondence of the obtained concentrations and requires a reliable choice of sampling parameters considering the site-specific boundary conditions. As a final consideration, the available literature showed the wide interest in I/O studies on the assessment of particulate matter chemical components between indoor and outdoor environments, in different contexts, especially schools [34,45,49,61,68,83]. In particular, a broad investigation of PM-bound PAHs is widely reported by recently-published papers [87][88][89][90] and a dedicated review on such topics is under consideration by the authors, given the increasing interest of the scientific community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, important to underline that the good correlation founded in some studies [40] does not necessarily imply a complete correspondence of the obtained concentrations and requires a reliable choice of sampling parameters considering the site-specific boundary conditions. As a final consideration, the available literature showed the wide interest in I/O studies on the assessment of particulate matter chemical components between indoor and outdoor environments, in different contexts, especially schools [34,45,49,61,68,83]. In particular, a broad investigation of PM-bound PAHs is widely reported by recently-published papers [87][88][89][90] and a dedicated review on such topics is under consideration by the authors, given the increasing interest of the scientific community.…”
Section: Discussionmentioning
confidence: 99%
“…In working environments, PM size distribution, concentrations, and chemical properties are even more site-specific than in residential ones as these depend on the used materials, productive methods, and working typologies. Extensive literature on school environments, partially for assessing children's exposure (i.e., the tendency for health impairments, and the large percentage of daytime spent in those spaces) and as a major working sector for the number of employees, is found [14,[33][34][35].…”
Section: Brief Summary Of the Main Characteristics Of Pm In Indoor Anmentioning
confidence: 99%
“…5 In addition to the specific sources related to indoor activities, indoor air quality (IAQ) has been shown to have a direct association with the quality of outdoor air 6 ; the contribution due to the infiltration of pollutants from outdoor sources has been analyzed in some previous studies, some of which focused on particulate matter (PM). 9,10 Recently, data related to IAQ in schools were collected in different European countries [11][12][13][14] and several studies have shown that children who study and live in industrial areas have a tendency to present increased respiratory symptoms when compared to those living in other areas. 9,10 Recently, data related to IAQ in schools were collected in different European countries [11][12][13][14] and several studies have shown that children who study and live in industrial areas have a tendency to present increased respiratory symptoms when compared to those living in other areas.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Particularly in very polluted areas, such as industrial sites or urban areas of developing countries, indoor air may reflect the poor quality of the outdoor atmosphere, and domestic and school environments, where urban populations-and children in particular-typically spend up to 90% of their time, thus requiring special attention. 9,10 Recently, data related to IAQ in schools were collected in different European countries [11][12][13][14] and several studies have shown that children who study and live in industrial areas have a tendency to present increased respiratory symptoms when compared to those living in other areas. 15,16 IAQ problems in school environments are more serious than in other categories of buildings.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Therefore, the majority of exposure to fine particulates occurs indoors, 9 and the outdoorto-indoor transportation process of fine particles can greatly affect population exposure. [10][11][12][13] Ammonium nitrate is the main inorganic constituent in outdoor and indoor environments. Previous studies have shown that ammonium nitrate contributed 13% to outdoor total bulk aerosols all year round in Beijing.…”
Section: Introductionmentioning
confidence: 99%